Branding Strategy to Improve the Competitiveness of Omah Batik Nusantara MSMEs in Modern Market: Strategi Branding untuk Meningkatkan Daya Saing UMKM Omah Batik Nusantria di Pasar Modern - Aileena Solicitor Costa Rica El Chidtian; Pungky Febi Arifianto; Dita Megasari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Batik, as Indonesia's cultural heritage, has become an important part of people's lives and drives the growth of the batik industry, including MSMEs such as Omah Batik and Ecoprint Nusantria. These MSMEs face major challenges in terms of weak branding, inconsistent visual identity, and less than optimal use of digital marketing, making it difficult to compete in an increasingly competitive market. To overcome this, a consistent branding strategy and maximum use of social media can help improve branding quality and expand market share. Community service activities at Omah Batik and Ecoprint Nusantria involve discussions, site reviews, counseling, consultations, training, and mentoring to improve understanding of visual branding, packaging design, and digital marketing. The results of the community service show that strengthening the branding of Omah Batik and Ecoprint Nusantria can be done by improving a consistent and authentic visual identity, as well as improving social media management to strengthen brand awareness. Improvements are made by focusing on a more attractive logo design and relevant Instagram content.